Bangunan Indis Sebagai Penanda Kota Surabaya, Jawa Timur: Bangunan Indis sebagai Penanda Kota Surabaya, Jawa Timur - Chawari, Muhammad; Pratama, Henki Riko; Priswanto, Hery; Tjahjono, Baskoro Daru (Berkala Arkeologi, 2023)
Surabaya has experienced a long historical journey, starting from the influence of the Javanese Kingdoms, Singasari, successively under the rule of the Majapahit, Demak, Pajang, and then finally the Islamic Mataram. The new chapter of Surabaya was under foreign influence when the Dutch came to the beginning of the 17th Century. The impact of the Dutch colonialism was the large number of Indische buildings in the Old City area of Surabaya. This arcticle explains the research result based on a qualitative method and inductive reasoning. towards the distribution of Indische buildings in the City of Surabaya.  It is divided into the Old Surabaya and New Surabaya cluster areas. Apart from the condition of most of the Indische buildings today that has undergone many changes, several Indische buildings that still exist today are considers as city landmarks of Surabaya. Eventhough, along with the development of the city of Surabaya, many Indische buildings have been dismantled and replaced with modern buildings.